Calculation of HAS-BLED Score Is Useful for Early Identification of Venous Thromboembolism Patients at High Risk for Major Bleeding Events: A Prospective Outpatients Cohort Study - Rief, Peter; Raggam, Reinhard Bernd; Hafner, Franz; Avian, Alexander; Hackl, Gerald; Cvirn, Gerhard; Brodmann, Marianne; Gary, Thomas (Seminars in Thrombosis and Hemostasis, 2018)
The aim of this study was prospective evaluation of the performance of the HAS-BLED score in predicting major bleeding complications in a real-world outpatient cohort, during long-term anticoagulation for venous thromboembolism (VTE), treated with a broad spectrum of anticoagulants. We analyzed 111 outpatients objectively diagnosed with VTE and treated long-term with various anticoagulants. Patients were grouped in three cohorts based on the anticoagulant regimen. Calculation of the HAS-BLED score and documentation of bleeding events were performed every 6 months for 1 year. Patients with a HAS-BLED score ≥ 3 had an increased risk for major bleeding events (odds ratio [OR]: 13.05, 95% confidence interval [CI]: 0.96–692.58, p = 0.028) and a trend to higher risk for minor bleeding events as well (OR: 2.25, 95% CI: 0.87–5.85, p = 0.091) when compared with patients with a HAS-BLED score < 3.This indicates that a HAS-BLED score ≥ 3 allows for identification of patients with VTE on long-term anticoagulation at an increased risk for major bleeding events, irrespective of the anticoagulant agent used.
Keywords: HAS-BLED score; venous thromboembolism; bleeding complications; anticoagulant treatment